EXPERIMENTAL TECTONICS: FROM SIR JAMES HALL TO THE PRESENT - Ranalli G. (My University, 2001)
The subject of experimental tectonics is the study of geodynamic processes by means of laboratory scale models. The first roughly scaled experiments were performed by Sir James Hall about two centuries ago, in the intellectual atmosphere generated by the appearance of Hutton's Theory of the Earth (Hutton, J., 1795. Theory of the Earth, with Proofs and Illustrations, Vols. I & II. Cadell & Davies, Edinburgh). Their aim was to test the hypothesis that the folding of originally horizontal strata is the result of lateral compression. The idea to test hypotheses by laboratory experiments had already been applied by Hall to petrological problems (crystallization and melting) not involving scaling. Interestingly, however, he constructed a scale model of a Gothic cathedral, using a line of reasoning parallel to that used in his tectonic experiments. From these beginnings, the theory and practice of scale models have grown to become an important part of an integrated approach to the study of geodynamics. One topic which is at present the focus of much attention is the choice of model materials correctly scaling the temperature dependence of lithospheric materials. As an example, a brief discussion is offered of two geodynamic problems where the application of scale models is proving very fruitful: the initiation and time-history of subduction of oceanic and continental lithosphere, and the tectonic evolution of orogenic wedges.